Fiqh–Sufism Dialectics in Wahidiyah Teachings: An Integrative Model of Islamic Legal Thought in Indonesia - Asmik Nasikah; Ahyak Ahyak; Iffatin Nur; Syamsu Ni'am; Rohmatulloh Rohmatulloh (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2026)
This article examines the dialectical integration of fiqh (Islamic jurisprudence) and Sufism (taṣawwuf) within Wahidiyah teachings in Indonesia and critically explores its implications for contemporary Islamic legal thought. Employing a qualitative normative-legal approach combined with philosophical analysis, this study analyzes Wahidiyah doctrinal texts alongside classical fiqh literature and authoritative Sufi works through deductive legal reasoning, maqāṣid al-sharīʿah analysis, and ethical–spiritual interpretation. The findings demonstrate that Wahidiyah articulates a systematic and operational integrative framework in which fiqh provides normative structure and legal certainty, while taṣawwuf functions as an ethical–spiritual orientation that animates legal reasoning and practice. This integration is concretely structured through a hierarchical sequence of principles—lillāh–billāh, li al-rasūl–bi al-rasūl, li al-ghawth–bi al-ghawth, yuʿṭī kulla dhī ḥaqqin ḥaqqah, and taqdīm al-aham fa al-aham thumma al-anfaʿ fa al-anfaʿ—aligning intention, authority, obligation, and priority within Sharīʿah boundaries. Departing from previous studies that predominantly frame Wahidiyah as a devotional or cultural Sufi movement, this article conceptualizes Wahidiyah as an integrative model of Islamic legal philosophy. It contributes theoretically by demonstrating how Sufi ethical consciousness can be methodologically incorporated into jurisprudential reasoning without undermining legal certainty. Methodologically, the study offers a maqāṣid-oriented analytical framework for examining spiritually grounded legal practices. Practically, it provides an alternative paradigm to rigid legalism and unstructured mysticism by showing how spirituality, legal normativity, and ethical responsibility can be systematically harmonized in contemporary Muslim life. By positioning Wahidiyah as a transferable model of fiqh–tasawwuf dialectics, this research advances contemporary Islamic legal theory and offers a contextually grounded approach to developing spiritually informed yet normatively coherent jurisprudence in plural Muslim societies